A Pragmatic Approach In Teaching Speaking Skills for Vocational High School Students - Anita; Hidayani, Selnistia; Nuraeni Silfani, Ani; Razali, Khairil (English Education Department, 2023)
English proficiency is essential for international communication and is highly valued in the industrial world. However, vocational school students often struggle with their English-speaking abilities. To address this issue, a pragmatic approach to English language teaching is proposed. Pragmatics focuses on effective communication by considering cultural contexts and is believed to enhance speaking skills. The study utilizes a case study approach in two vocational schools, collecting data from students and teachers through questionnaires and interviews. The findings reveal differences in perceptions between teachers and students, highlighting the students' lack of understanding of teaching activities. The pragmatic approach is seen as a solution to improve students' speaking skills by incorporating language theories into real-life contexts. The study suggests the importance of teacher preparation, comprehensible instruction, and alignment of perceptions between teachers and students for effective teaching of speaking skills. The implementation of the pragmatic approach can be achieved by integrating comprehension of language structures and content, setting specific targets, and utilizing appropriate teaching materials.